ANALISIS PERSEPSI MASYARAKAT TERKAIT PROGRAM KELUARGA HARAPAN (STUDI KASUS DI DESA SAMPURAN KECAMATAN MUARA KABUPATEN TAPANULI UTARA) - Rajagukguk, Anggun N; Rajagukguk, Jonson; Degodona, L. Primawati; Panjaitan, Maringan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze public perceptions regarding the Family Hope Program (PKH) in Sampuran Village, Muara District, North Tapanuli Regency. The Family Hope Program (PKH) is a social assistance program that is expected to reduce poverty rates and improve community welfare through the provision of conditional cash assistance. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observations, and documentation studies. Research participants consisted of beneficiary families (KPM), community leaders, and other related parties. The results of the study show that public perceptions of PKH in Sampuran Village vary, with most beneficiaries considering this program to be helpful in meeting basic needs, especially in education and health. However, there are also negative perceptions that arise related to the selection procedure which is considered non-transparent and uneven. In addition, some people feel that the assistance provided is still insufficient to significantly improve their standard of living. This study concludes that although PKH has a positive impact on the welfare of beneficiaries, there are still challenges in the implementation of the program that need to be improved to achieve more optimal goals.